An analysis of the incidence, causes and preventative approaches to gram-negative bloodstream infections of hepatopancreatobiliary origin. Issue 3 (May 2021) - Majeed, Mustafa; Ward, Harry; Wade, Cian; Butcher, Lisa; Soonawalla, Zahir; Bond-Smith, Giles
Background: Gram-negative bloodstream infection (GNBSI) is a threat to public health in terms of mortality and antibiotic resistance. The hepatopancreatobiliary (HPB) cohort accounts for 15%–20% of GNBSI, yet few strategies have been explored to reduce HPB GNBSI. Aim: To identify clinical factors contributing to HPB GNBSI and strategies for its prevention. Methods: We performed a retrospective analysis of 433 cases of HPB GNBSI presenting to four hospitals between April 2015 and May 2019. We extracted key data from hospital and primary care records including: the underlying source of GNBSI; previous documentation of biliary disease; and any previous surgical or non-surgical management. Findings: Out of 433 cases of HPB GNBSI, 388 had clear evidence of HPB origin. The source of GNBSI was related to gallstone disease in 282 of the 388 cases (73%) and to HPB malignancy in 70 cases (18%). Of the gallstone-related cases, 117 had previously been diagnosed with symptomatic gallstones. Of the 117 with a previous presentation, 93 could have been prevented with a laparoscopic cholecystectomy at the first presentation of gallstones, while 18 could have been prevented if intraoperative biliary tract imaging had been performed during a prior cholecystectomy. Of the 70 malignant cases, five could have been prevented through earlier biliary stenting, use of metal stents instead of plastic stents or earlier pancreaticoduodenectomy. Discussion: The incidence of HPB GNBSI could be reduced by up to 30% by the implementation of alternative management strategies in this cohort.